Designing a Web-Based Therapy Aid Model for Non-Pharmacologists Stroke with Muscle Strength Disorder - Rr Hajar Puji Sejati; Rodhiyah Mardhiyyah (Association for Scientific Computing Electrical and Engineering, 2019)
This research will discuss a web-based stroke therapy model to display examples of online therapeutic movements. This therapy is expected to help the patient's attendant to perform the therapy independently. The attendant must consult with a physiotherapist/doctor to determine the appropriate therapy. This research is motivated by the results of focus group discussions with physiotherapy to get a positive response and an acceptable value of 80%. Results of focus group discussions suggest for mobile-based development of the model. Based on these suggestions, the design of the model in this study will be developed based on the web. A web-based application is expected to simplify the distribution process of expert system models for non-pharmacological stroke therapy tools.